PERANCANGAN FIXTURE IN JIG SEBAGAI ALAT BANTU PROSES PRODUKSI CASEBASE DI PT TEAM METAL INDONESIA - Efendi, Anton; Hasibuan, Rizki Prakasa (Computer Science and Industrial Engineering, 2022)
PT.Team Metal Indonesian (TMI) was established in 1997 in the field of manufacturing modular mechanical, electrical, and sub assys through various processes using machines to keep the survive and develop by innovating to improve the quality and quantity of production. Most of the production line used by this company uses machines with human labor as its operator. One of them is the bottom product, the open array case that continues to increase the number of production. But this process has several principal problems, namely, the low output and the high level of reject caused during the machining process. With the Quality Function Deployment method that is oriented to the Matrix House of Quality as a basis for obtaining information about consumer needs that are the basis of the design and development of the tool. So the purpose of this study was to design a fixture in the form of a fixture to help the process of creating material when the machining process was carried out. By applying the Quality Function deployment method in the design process, the results obtained are Portable Pokayoke / Mistake Proofing fixture with the results of an increase in output by 32% with better product quality